2021
DOI: 10.1055/s-0040-1722651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes after Mitral Valve Repair with the Physio II Annuloplasty Ring

Abstract: Background Mitral valve (MV) repair with annuloplasty is the standard of care in patients with primary degenerative mitral regurgitation (DMR). Newer generations of annuloplasty rings have been developed with the goals of closer reproduction of native annular geometry and easier implantation. This study investigates the short-term and 5-year clinical outcomes of MV repair with the Carpentier-Edwards (CE) Physio II annuloplasty ring. Methods This is an observational study including a total of 486 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Castillo et al reported no MR in 94.5% and mild MR in 5.5% of 744 patients at predischarge; 98% of patients were using a CE Physio I or II ring ( 3 ). Noack et al have shown that 80% of no MR, 18% of mild MR at discharge, and the rate of not requiring re-MV operation at one and four years were 96.2% and 94.0%, respectively, after MVr with a CE Physio II in 486 patients ( 18 ). David et al found only three patients (0.3%) with moderate MR among 840 patients who underwent MVr using various annuloplasty devices ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Castillo et al reported no MR in 94.5% and mild MR in 5.5% of 744 patients at predischarge; 98% of patients were using a CE Physio I or II ring ( 3 ). Noack et al have shown that 80% of no MR, 18% of mild MR at discharge, and the rate of not requiring re-MV operation at one and four years were 96.2% and 94.0%, respectively, after MVr with a CE Physio II in 486 patients ( 18 ). David et al found only three patients (0.3%) with moderate MR among 840 patients who underwent MVr using various annuloplasty devices ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ashikhmina observed SAM immediately after cardiopulmonary bypass in 13% of the patients (98 of 761 patients) [ 2 ]. Loulmet and colleagues reported an incidence of SAM of 4% (77 of 1906) [ 4 ] and Noack et al of 2.1% (10/486) [ 6 ]. Some morphologic criteria of valves may be predisposed to develop SAM after repair, such as abundant leaflet tissue, steep aortic-mitral angle, septal hypertrophy, and small c-sept distance.…”
Section: Discussionmentioning
confidence: 99%
“…They observed a 30-day mortality of 2.1% and reported a survival and freedom from reoperation at 4 years of 93.6 and 93.8%, respectively. Recently, Noack et al reported mid-term results of mitral valve repair using the Physio II ring [ 6 ]. They demonstrated a freedom from MV related reoperations of 96.3 and 94% at 1 and 4 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation